2021
DOI: 10.3389/fmicb.2021.713523
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal Limitation Plays Stronger Role in the Community Assembly of Fungi Relative to Bacteria in Rhizosphere Across the Arable Area of Medicinal Plant

Abstract: Understanding the ecological patterns of rhizosphere microbial communities is critical for propelling sustainable agriculture and managing ecosystem functions by exploiting microorganisms. However, this knowledge is still unclear, especially under host-associated large-scale and regarding the comparison between bacteria and fungi. We examined community assembly processes and community characters including environmental thresholds and co-occurrence patterns across the cultivatable area of Panax notoginseng for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 96 publications
6
20
0
Order By: Relevance
“…We demonstrated that the two main taxonomic groups of vineyard soil microbiomes are regulated by distinct assembly processes over a range of spatial scales. In line with our expectations, fungal metacommunities displayed stronger In line with recent investigations of soil microorganisms across a range of ecosystem types, we have shown that bacterial and fungal communities in vineyard soils display assembly patterns that are consistent with their known ecology and body size [18,20,30,31]. These findings have both fundamental and applied implications.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We demonstrated that the two main taxonomic groups of vineyard soil microbiomes are regulated by distinct assembly processes over a range of spatial scales. In line with our expectations, fungal metacommunities displayed stronger In line with recent investigations of soil microorganisms across a range of ecosystem types, we have shown that bacterial and fungal communities in vineyard soils display assembly patterns that are consistent with their known ecology and body size [18,20,30,31]. These findings have both fundamental and applied implications.…”
Section: Discussionsupporting
confidence: 91%
“…This is also reflected in the larger fluctuations that we observed in the abundance of fungal taxa between years. In addition, and in line with other studies in both natural and managed ecosystems, fungal populations in soils displayed limited dispersal capacity [20,22,31]. In agreement with theoretical predictions, limited dispersal ability and smaller population sizes likely combined to Relative abundance (log) Occurrence frequency increase the influence of stochasticity and drift on fungal dynamics [66].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Likewise, these experiments also showed that in the case of fungi, the effect of the host species has a stronger force in the acquisition of the fungal communities in the rhizosphere from soil ( Hannula et al, 2019 ; Thiergart et al, 2020 ). It is important to note that in the case of fungi, various studies point to the existence of stochastic factors that randomly determine the assembly of fungal communities in the rhizosphere, the main one being the dispersal ability of fungi in the soil ( Hussain et al, 2021 ; Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these deterministic factors, soil microbial communities can also be affected by stochastic processes that generate species compositional patterns indistinguishable from those produced at random ( Tripathi et al, 2018 ; Richter-Heitmann et al, 2020 ; Hussain et al, 2021 ; Zhang et al, 2021 ). These stochastic processes involve random proliferation, death, and dispersal events ( Tripathi et al, 2018 ; Richter-Heitmann et al, 2020 ; Hussain et al, 2021 ; Zhang et al, 2021 ). Then, the ratio between stochastic and deterministic effects on microbial communities affects the species diversity and composition over temporal and spatial scales ( Tripathi et al, 2018 ; Richter-Heitmann et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%